(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Consumers face the task of purchasing medicine. Consumers usually choose from one of the two types of pharmaceutical drugs: brand names and generics. However, the budget can also play an essential factor. Therefore, consumers must take the medicine properly for their health and always read the right dosage of the medicine they are taking. The study utilized a quantitative research method design of 50 consumers of Generic and Branded medicines residents of Amparo Caloocan City. This study used a purposive sampling technique. The study used survey questionnaires to gather information and answer the following statistical tools: frequency and percentage, weighted mean, and T-test for the Correlation Coefficient r. The study revealed that most generic aged 36-45 years and above are married females, employed and compensated in the amount of 5,000 below, while consumers of branded aged 36-45 years old are female single, employed and compensated in the amount 10,000 - 15,000. The factors or variables associated with how generic and branded medicines affect consumer buying behaviour, The factors or variables associated on how generic and branded medicines affect consumer buying behaviour in terms of place, strongly agree for generic medicines and very strongly agree with branded medicines, Price, are very strongly agree on both consumer of generic and branded medicines, branding, strongly agree for generic medicines and very strongly agree for branded medicines and promotions, strongly agree for generic medicines and very strongly agree for branded medicines. As for the significant difference between the two groups of respondents, it reveals that the overall weighted mean is 4.37 for consumers of generic and branded medicines. The computed clearly shows that consumers of generic medicines and branded obtained a t-test value of -4.67, the level of its significance is 0.05, and the p-value is 0.0185, while the degree of freedom is 3. Its tabular/critical value is 3.182. The decision would be to reject the hypothesis and interpret it as significant. The t-computed is greater than the tabular p-value; therefore, reject the hypothesis. There is a significant difference between the assessment of the two groups of respondents on the comparative analysis between branded and generic in terms of place, Price, branding, and promotions. The most definite problem may be forwarded to WellQuest pharmacy. They should have free medical check-ups one to two times a month, recommended by the researchers, and tied-up bundles for the people who want to save money. WellQuest drug stores should have priority lanes for pregnant, senior citizens, and PWD.